The Agri-Food trade in Spain: specialization and international competition - María Josefa Garcia Grande; José María López Morales (European Regional Science Association (ERSA), 2015)
Agri-food Industry, as the sum of the Agriculture, Livestock, Forestry and Fishing and Food Industry (Food, Beverages and Tobacco) is, except some service activities, the highlight industry of the Spanish economy, not only for their GVA (5.3% in 2013) and employment contribution (6.4% on the same date), but above all for its relevant presence in international markets. The importance of Agri-Food Industry in the Spanish economy is much higher than this sector has in the European Union (EU-28) or in the Euro Area (3.8% and 3.7% of GDP, respectively), and its contribution in the EU agri-food production (11.8% in 2012) reaches a similar level of the great European countries (Germany and Italy -11.8 and 12.6 per 100, respectively) and only below the contribution of France -16.2 per 100-. Internationally, Spain is one of the major exporting countries of the world. It is the second largest exporter of Fruits, the third exporter of Legumes and other edible vegetables, the fifth exporter of Animal, vegetable fats and oils, sixth exporter of Meat and seventh of Beverages. The aim of this paper it is to analyze the territorial specialization in the agri-food trade and to study the diversification both in respect of exported products as in regard to customers who purchase those products. The final purpose will be to determine the competitive advantages and weaknesses, both from a sectorial or spatial perspective, to determine which possibilities of expansion shows this trade and what policy measures should be taken to correct the weaknesses of the sector and enhance the strengths of some activities with significant international presence. To perform the analysis, we use information about global imports and exports (annual frequency) from Comtrade Database, United Nations, which uses the Standard International Trade Classification (SITC Rev.3). We work with a disaggregation level of 2 and 3 digits. For certain aspects, we will use information from DataComex, from Ministry of Economy and Finance of Spain; that it is consistent with that provided by Comtrade.
Keywords: F; Q; R; 330; Agri-Food; Food Industry; Agri-Food imports and exports; Food; Beverages and Tob